Nanocápsulas: preparação, caracterização e marcação com 99mTC-HMPAO para estudos de biodistribuição em modelo experimental de inflamação - Maira Alves Pereira (2006)
The identification and the correct exclusion of inflammatory foci is veryimportant for the adequate treatment of patients who may bear theseprocesses. Techniques of nuclear medicine are known for their sensibility in thediagnosis of pathological conditions such as inflammation. Someradiopharmaceutical drugs have been utilized for this purpose, but theappearance of side effects, the difficulty of preparation and manipulation of these radioactive tracers have motivated the search for better diagnostic agents. The present work describes the preparation, characterization and labeling of conventional and surface-modified nanocapsules (NCs) with 99mTc- HMPAO to identify the inflammatory foci. The size, homogeneity and zetapotential of the NC preparations were determined with a Zetasizer (MalvernInstruments, UK). The morphology and the structural organization wereevaluated by atomic force microscopy (AFM). The stability of the NCs wasdetermined in vitro in plasma. Male Wistar rats weighing between 180 and 210g were utilized for the development of inflammatory foci induced by 1%carrageenan and for biodistribution studies. The results of the encapsulation showed that the use of methylene blue lead to a significant increase in theencapsulation of 99mTc-HMPAO in the oily nucleus of these nanostructures (p _0.05). The average diameter calculated by photon correlation spectroscopy (PCS) varied from 216 to 323 nm, while the average diameter determined by AFM varied from 238 to 426 nm. The diameter/height ratio suggested a greater homogeneity of the surface-modified nanocapsules. The in vitro liberation of the99mTc-HMPAO in plasma medium was faster for the conventional NCs than for the surface-modified NCs. For the latter, 60% of the radioactivity remained in their interior, even after 12 hours of incubation. The biodistribution studies demonstrated a greater uptake of the surface-modified 99mTc-HMPAO-NCs bythe inflamed paws than that of the respective controls. There was no significantdifference in the uptake of conventional 99mTc-HMPAO-NCs and of free 99mTc-HMPAO by inflamed and control paws. The results suggest that the surfacemodified99mTc-HMPAO-NCs could be utilized for the identification ofinflammatory foci.